A platform to deploy customized scientific virtual infrastructures on the cloud. (20th May 2015) - Caballer, Miguel; Segrelles, Damián; Moltó, Germán; Blanquer, Ignacio
Summary: This paper presents a software platform to dynamically deploy complex scientific virtual computing infrastructures, on top of Infrastructure as a Service Clouds. The platform orchestrates different services to provision the virtual computing resources. It dynamically installs the appropriate software to satisfy the requirements of a researcher, both on public and on‐premise Clouds. The platform provides a web interface to enable the users to easily manage the life cycle of virtual infrastructures. It enables users to define infrastructures, share them with other users, deploy and relinquish them, add or remove resources dynamically, create and share application recipes, and so on. The paper also describes three case studies to deploy complex infrastructures, namely, a Hadoop cluster, a single‐node to perform Next Generation Sequencing and a gateway for users to access the European Grid Infrastructure. This platform promotes a better use of on‐premise hardware resources of a research center by allocating the computing resources just‐in‐time to the specific life time of the virtual infrastructures as well as the deployment of the very same infrastructures on a public Cloud. Copyright © 2015 John Wiley & Sons, Ltd.